Kadar lipoprotein (A) dan kadar sensitivitas tinggi C-reaktif protein pada penderita penyakit jantung koroner yang dilakukan angiografi - Dian Effrida Lubis; Zulfikar Lubis; lsfanuddin Nya Kaoy (Majalah Kedokteran Nusantara The Journal Of Medical School, 2015)
Introduction : CAD marked by coronary artery blockage by fatty deposits that gather within the cell, either partially or totally from one or more of the coronary arteries. CAD is defined as the presence of stenosis > 70% with angiography examination. Understanding of atherosclerosis began after the hypothesis of response to injury and hypothesis of lipid disorder (lipid theory). Merge both this hypothesis can explain better the occurrence of atherosclerosis.This research aims to find out if there are differences in the levels of hs-CRP and Lp (a) in CAD patients compared with the control group. And determine whether the concentrations of hs-CRP and Lp(a) correlate with the CAD. Methods :This cross sectional study was conducted in 30 people with CADwhen angiography showed coronary artery stenosis>70% and coronary artery stenosis > 70% as a controlfrom Juli up to September 2014. Blood samples were taken after angiography to checked hs-CRP and Lp(a) levels Results : In this study,we found significant differences in hs-CRP level betwen CAD patients (35.29±42.79) and control group (2.96±1 .88) and also we found significant differences in Lp{a) level between CAD patient (79.09±40.18) and control group 17.21±9,74) with <0.05. The study also found a strong correlation between hs-CRP and Lp (a) with CAD patient (r-0.835 and p < 0.05), (r =Q.713, p < 0.05), respectively Conclusion :There were a significant difference in the levels of hs-CRP and Lp (a) in CAD group compared to the control groupThere is a strong correlation between hs-CRP and Lp (a) with the CAD. Key words : CAD, angiography, hs-CRP, Lp(a)